Preparing the public servant for the new government - Guina, Carolina S. (1986)
In order to implement the goals of the Aquino administration, there is a need to re-orient the bureaucracy into a new value-system that is responsive to the demands of the clientele/public. The existing bureaucracy which has been long conditioned to the system of the previous dispensation, is faced with the task of reordering and realigning itself with the visions of the Aquino administration: a government unbridled with graft and corruption, inefficiency, unprofessionalism, alienation and irrelevance. The question raised is whether mere value-system can significantly mark the transformation without a radical departure from the established structure of power relations.
Keywords: Administrative reform; Political reform